Delayed treatment of unstable proximal interphalangeal joint fracture-dislocations with a dynamic external fixator. Issue 10 (October 2015) - Shen, Xiao Fang; Mi, Jing Yi; Rui, Yong Jun; Xue, Ming Yu; Chou, Jiandong; Tian, Jian; Chim, Harvey
Abstract Background Fracture-dislocations of the proximal interphalangeal joint (PIPJ) remain a challenging problem to treat. Although there are a number of papers describing the use of dynamic external fixators and force couples for treatment of unstable PIPJ fracture-dislocations acutely, the literature is scarce on delayed treatment of PIPJ fracture-dislocations, where malunion of the articular surface may theoretically compromise postoperative range of motion (ROM) at the PIPJ. The purpose of this study was to evaluate the effectiveness of dynamic distraction external fixation (DDEF) for the delayed treatment of PIPJ fracture-dislocations at least 3 weeks after the inciting injury. Methods Ten consecutive patients were treated with delayed DDEF between 2010 and 2013. Postoperative ROM at the PIPJ was measured. Disabilities of the Arm, Shoulder and Hand (DASH) score and Michigan Hand Outcomes Questionnaire were administered to all patients postoperatively. Results Mean time from injury to surgery was 27.5 days. The mean follow-up period was 23.7 months (range 10–36). The mean active ROM at the PIPJ on final postoperative follow-up was 83.9° (range 52–100). None of the patients experienced pin-tract infections. Mean DASH score was 3.7 + 3.4 and mean Michigan Hand Outcomes Questionnaire score was 97.3 + 3.0. All patients returned to work and resumed normal activities. Conclusions Delayed treatment of unstable PIPJ fracture-dislocations with a DDEF is effective in restoring function to the PIPJ. Nascent malunion of the PIPJ articular surface does not compromise postoperative outcomes and the joint surface undergoes remodelling over time to restore a smooth and functional articular surface.